Management buy-outs as an instrument of privatization in Eastern Europe - Harald Sondhof; Markus Stahl (Intereconomics, 1992)
Privatizing government enterprises is one of the most difficult tasks in the transformation process taking place in the former socialist economies. What contribution do management buy-outs have to make in coping with that task?
Keywords: 330; System Transformation